Information Security and Privacy Quick Reference - The Essential Handbook for Every CISO, CSO, and Chief Privacy Officer - Shelley Joe; Chapple Mike; Stewart James Michael (John Wiley & Sons, 2025)
A fast, accurate, and up-to-date desk reference for information security and privacy practitioners everywhere.Information security and privacy roles demand up-to-date knowledge coming from a seemingly countless number of sources, including several certifications-like the CISM, CIPP, and CISSP-legislation and regulations issued by state and national governments, guidance from local and industry organizations, and even international bodies, like the European Union.This is an updated, convenient, and accurate desk reference for information privacy practitioners who need fast and easy access to the latest guidance, laws, and standards that apply in their field. This book is the most effective resource for information security professionals who need immediate and correct solutions to common and rarely encountered problems.This is a must-have resource for CISOs, CSOs, Chief Privacy Officers, and other information security and privacy professionals seeking a reliable, accurate, and fast way to answer the questions they encounter at work every single day.